P113 The prevalence of depression and anxiety at first presentation to rheumatology outpatients. (23rd April 2022) - Arumalla, Nikita; Littlewood, Rebecca; Chen, Winnie; Garrood, Toby
Abstract: Background/Aims: Depression and anxiety are more common in patients with rheumatic diseases and have been associated with higher levels of fatigue, pain and levels of physical disability. Although this has been described in distinct rheumatic conditions, the burden of psychological morbidity across the diseases presenting to rheumatology outpatients is not as well known. The prevalence of anxiety and depression in the UK was reported to be 5.9% and 3.3% respectively. Here, we report rates of depression and anxiety in a cross-section of new patients referred to rheumatology outpatients. Methods: All new patients referred to a rheumatology outpatient clinic in London, UK for a 10-week period in February to May 2019 received a digital pre-appointment questionnaire which included Patient Health Questionnaire (PHQ8) and Generalised Anxiety Disorder Questionnaire (GAD7) questionnaire for detecting depression and anxiety respectively. A retrospective analysis was performed to assess the prevalence of significant depression and/or anxiety in various rheumatic diseases, defined as PHQ8 or GAD7 ≥ 10, signifying at least moderate depression or anxiety respectively. Results: 464 patients completed the questionnaire, 338 female (73%), with a mean ± SD age of 44.3 ± 13.6 years. 41.2% of patients screened positive for depression and 26.5% for anxiety, with 24.4% screening positive for both. Of the patients screening positive for anxiety, 91.9% were also depressed. The four most prevalent conditions were rheumatoid arthritis (RA, 8.6%), osteoarthritis (OA, 15.3%), psoriatic arthritis (PsA, 8.4%) and fibromyalgia (FM, 24.4%). The prevalence of at least moderate depression and/or anxiety in RA, OA, PsA and FM was 22.5%, 35.2%, 46.1% and 77% respectively. Logistic regression determined odds ratios relative to RA for significant depression and/or anxiety as follows: OA 1.89 (95% CI 0.76-4.67), PsA 2.75 (1.02-7.41), FM 11.80 (4.91-28.36). Conclusion: The burden of psychological illness is high across the population of patients presenting to rheumatology outpatients. Our findings show significant prevalence of psychological illness at first presentation. Early identification of psychological distress is important as it can predict adverse long-term outcomes in patients with rheumatic conditions. These results justify an integrated approach between rheumatology and mental health services. Disclosure: N. Arumalla: None. R. Littlewood: None. W. Chen: None. T. Garrood: None.